2021
DOI: 10.1080/19491034.2021.1889858
|View full text |Cite
|
Sign up to set email alerts
|

HP1β carries an acidic linker domain and requires H3K9me3 for phase separation

Abstract: Liquid-liquid phase separation (LLPS) mediated formation of membraneless organelles has been proposed to coordinate biological processes in space and time. Previously, the formation of phase-separated droplets was described as a unique property of HP1α. Here, we demonstrate that the positive net charge of the intrinsically disordered hinge region (IDR-H) of HP1 proteins is critical for phase separation and that the exchange of four acidic amino acids is sufficient to confer LLPS properties to HP1β. Surprisingl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 46 publications
2
34
0
Order By: Relevance
“…Recently we found that HP1β shows phase separation properties in the presence of H3K9me3 histones in vitro ( 11 ). We next investigated its function in heterochromatin organization in cells.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently we found that HP1β shows phase separation properties in the presence of H3K9me3 histones in vitro ( 11 ). We next investigated its function in heterochromatin organization in cells.…”
Section: Resultsmentioning
confidence: 99%
“…For generation of HP1β −/− mESCs, the MINtag strategy was used as described previously ( 11 , 22 ). After generation of the MIN-tagged line, the attB-RFP-Stop-PolyA was inserted into the N-terminus of the endogenous HP1β attP/attP locus by Bxb1 mediated recombination.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The recent experimental studies have provided a fresh new perspective on the mechanistic roles of HP1a by showing that solutions of HP1a can undergo spontaneous liquid–liquid phase separation [ 15 , 16 , 17 ]. Phase separation of HP1a has a distinct electrostatic origin confirmed by the fact of HP1a condensing in vitro by the change of ionic conditions [ 15 ], the addition of phosphate groups [ 16 ] or sequence mutations [ 18 , 19 ] in the disordered hinge regions.…”
Section: Introductionmentioning
confidence: 99%